Role selection and team performance - David J. Cooper; Matthias Sutter (Institute for the Study of Labor (IZA), 2011)
Team success relies on assigning team members to the right tasks. We use controlled experiments to study how roles are assigned within teams and how this affects team performance. Subjects play the takeover game in pairs consisting of a buyer and a seller. Understanding optimal play is very demanding for buyers and trivial for sellers. Teams perform better when roles are assigned endogenously or teammates are allowed to chat about their decisions, but the interaction effect between endogenous role assignment and chat unexpectedly worsens team performance. We argue that ego depletion provides a likely explanation for this surprising result.
urn:nbn:de:101:1-201108093231
Keywords: C91; C92; 330; role selection in teams; team performance; takeover game; winner's curse; communication; experiment